A Comprehensive Analysis of The Reformed Education System: National Education Policy - Shoryaditya; Jain, Seema (International Journal of Psychosocial Rehabilitation, 2024)
A comprehensive set of reforms aimed at revolutionizing India’s educational system is the New Education Policy (NEP) 2020. The goal of the strategy is to address the issues that the existing system is confronting, including low learning results and a dearth of emphasis on critical thinking and problem-solving abilities. The goal of the policy is to change education to make it more flexible, multidisciplinary, and comprehensive. Additionally, the policy seeks to encourage students’ critical thinking, creativity, and innovation. This essay offers a thorough analysis of the NEP 2020 and assesses how well it has improved India’s educational system. The review study’s foundation is a detailed examination of current literature, official documents, and data sources. The NEP 2020 has been praised as a historic initiative that will fundamentally alter the educational landscape. This study looks at how well the NEP 2020 accomplishes its objectives.